2022
DOI: 10.1007/s12649-022-01730-z
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Processed Kola Nut Husk Meal in Poultry Production: Effects on The Performance, Carcass, Biochemical Indicators, and Antioxidant Enzymes of Broiler Chickens

Abstract: This study looked at the effects of processed kola nut husks meal (PKHM) utilization as a feed ingredient on broiler chicken in a 42-day feeding trial. Kola nut pod husks were processed into a PKHM using ash treatment and rumen liquor fermentation. Three experimental diets were developed at both the starter and nisher phases, with PKHM included at 0, 4, and 8%, and dubbed diets 1, 2, and 3, respectively. In a fully randomised design, 240 Arbor Acres broiler chicks were randomly assigned to three treatments (10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Previous studies have indicated phytosupplements as growth promoters in animals and particularly broiler chickens (Olarotimi et al, 2022;Oloruntola 2022b;Valenzuela-Grijalva et al, 2017). According to this study, JKP and JLP supplements boosted growth performance in broiler birds fed diets contaminated with AF.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have indicated phytosupplements as growth promoters in animals and particularly broiler chickens (Olarotimi et al, 2022;Oloruntola 2022b;Valenzuela-Grijalva et al, 2017). According to this study, JKP and JLP supplements boosted growth performance in broiler birds fed diets contaminated with AF.…”
Section: Discussionmentioning
confidence: 62%